Improving mealtimes for paediatric intensive care children and families: A quality improvement initiative. Issue 4 (23rd October 2020) - De Monte, Malorie; Marty Petit, Emilie M. L.; Baudin, Florent; Zamor, Julia; Ford‐Chessel, Carole; Tume, Lyvonne N.; Bordet, Fabienne; Valla, Frederic V.
Abstract: Background: Many critically ill children can be fed orally at some point during their paediatric intensive care (PICU) stay, but reduced appetite and other factors may impact their intake. At home, oral feeding is usually delivered by parents, so involving parents more actively during mealtimes in the PICU may contribute to improved patient/family satisfaction. Aim: To assess the impact of a new "room service" initiative involving parents on mealtime quality and on both family and health care professional (HCP) satisfaction. Methods: A prospective, single‐centre, before‐and‐after intervention study was designed as part of a PICU quality‐of‐care improvement programme in 2013 to 2016. Two questionnaires assessing oral nutrition practices and family/HCP overall satisfaction were disseminated among the parents of critically ill children capable of oral feeding during their PICU admission and among the whole PICU HCP team (nurses, nurse assistants, and medical doctors). Categorical variables were compared using the chi‐square test, and Likert scales were compared between groups with the Mann‐Whitney‐Wilcoxon test. Results: the pre‐intervention surveys were completed by 97 of 130 (75%) HCPs and 52 families and the post‐intervention surveys by 74 of 130 (57%) HCPs and 54 families. After the intervention, a marked improvement was observed in the overall quality of meal service rating by both HCPs and families (medians and IQR: 5 (5‐7) to 7 (7, 8) and 6 (6‐8) to 8 (7‐9), respectively; P < .01) and also in parents' involvement; in children's, families', and HCP satisfaction; in meal‐dedicated facilities and equipment; and in perception that oral nutrition is an important aspect of PICU care. Conclusions: Implementation of an improved "room service" initiative in the PICU was feasible and improved the perceived quality of care and satisfaction around oral feeding. This family‐centred care initiative can be integrated in an overall quality improvement strategy.